Integrating Quality Management Practices to Drive Sustainable Competitive Advantage through SERVQUAL Dimensions in the Evolving Hospitality Sector - Shah, Bijaya Bikram; Aryal, Mukunda (Apex Journal of Business and Management, 2025)
This research investigation delves into the optimal blending of total quality management practices and SERVQUAL dimensions toward the establishment of a sustainable competitive advantage for the constantly changing and dynamic hospitality sector. The research examines the interdependence of Total Quality Management practice and the five service quality dimensions of Tangibility, Reliability, Responsiveness, Assurance, and Empathy, as the strategic model for facilitating customer satisfaction and loyalty. By throwing an example of mapping perceptual service outputs on operation quality inputs, it is the contention of this paper that it is most important that hotels record and ensure a holistic quality culture in order to distinguish themselves in an over-supplied scenario. The research applies synthetically created dataset, quoting customer feedback across a cross-section of segments of hotel (Luxury, Boutique, Budget). These 500-response data are quantified with descriptive and inferential statistical indicators in an SPSS simulation setting. Quantification of the size of each one of the SERVQUAL dimensions' contribution to customer satisfaction and loyalty values and empirically typed evidence supporting the theoretical model is attained by the process. The result puts Assurance and Responsiveness of utmost significance in the pursuit of sustainable competitive advantage, and though all the dimensions are useful, they are most useful. The study discovers alignment of existing quality procedures to customers' external frames as the bare secret of long-term success.